Robert Louis Stevenson : author of A child's garden of verses - Greene, Carol (Chicago : Childrens Press, 1994)
A biography of the Scottish author who produced many popular novels and poems including A child's garden of verses.
Includes index.
Elem. School Library Collection.
School Library Journal.
2.5
K-3.
K-3
Keywords: Stevenson, Robert Louis, -- 1850-1894 -- Biography -- Juvenile literature; Stevenson, Robert Louis, -- 1850-1894.; Stevenson, Robert Louis, -- 1850-1894.; Authors, Scottish -- 19th century -- Biography -- Juvenile literature; Authors, Scottish; Scottish authors -- Biography